From war to diplomatic parity in eleventh-century China : Sung's foreign relations with Kitan Liao - Wright, David Curtis, 1960- (History of warfare ;, 2005)
This is a study of war between Sung China and Kitan Liao, the treaty at Shan-yüan in 1005 that ended it, and the forms and textures of peaceful diplomatic contact between the two states that prevailed for the rest of the eleventh century.